Living wages and the welfare state : the Anglo-American social model in transition - Wilson, Shaun, 1971- (Bristol : Policy Press, 2021)
Addressing the rapidly shifting politics of the minimum wage in six English-speaking countries, Shaun Wilson analyses minimum wage policies within a political-economy narrative. Topical and poignant, this book identifies the success of living wage campaigns as central to both welfare state change and alternatives to the Basic Income.
Title from publisher's bibliographic system (viewed on 04 Jan 2022).
Keywords: Minimum wage -- Cross-cultural studies; Living wage movement; Welfare state -- Cross-cultural studies